ONTOLOGY OF ACCOUNTING EDUCATION IN THE STUDY OF ACCOUNTING IMPLEMENTATION - Muya Syaroh Iwanda Lubis; Ima Ima (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2023)
ABSTRACTNationalism and empiricism, because accounting uses thought to examine the data of accounting transactions used in the preparation of financial reports. This fact is something that can be answered accurately by the human senses. As a component of axiology or in accounting studies, accounting science is used as part of the accounting profession. Accounting science explains how financial reporting processes and transaction relationships affect each other in epistemology. The study examines accounting science from a theoretical perspective with a focus on epistemological aspects. This is crucial because philosophically accounting can be trapped in a science trap if it does not understand these aspects in a field of science. (Suwardi, 1999). The structure of the discussion in this study begins with a discussion of God's early command to carry out accounting. Next, we will discuss the philosophy of accounting from an epistemological point of view. The Islamic concept of accounting is discussed in the next section, and we will deduce the Islamic epistemological side of accountancy.Keywords: Ontology, Accounting Education, Implementation